Peningkatan Produksi ASI Pada Ibu Post Partum Melalui Tindakan Pijat Oksitosin - Anggraeni, Ayu Kurnia (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2024)
This study aims to look at the effect of oxytocin massage on breast milk production in postpartum mothers in the working area of Public Health Centers in Cikeusik. This study uses a pre-experimental research method with One Group Pre-Test-Post Test approach. Popolation in this research is pregnant women who have estimated delivery on June and July totally 30 person with samples using accidental sampling technique. Data collection in this study uses primary data to see the identity of respondents and secondary data by doing oxytocin massage on respondents. Data analysis was performed with the Shapiro-Wilk test and paired sample t-test. The results were obtained : (1) From 30 samples, there were 26 respondents with insufficient ASI production and 4 respondents who had sufficient ASI production. (2) from 30 respondents there were 7 respondents with insufficient ASI production and 23 respondents who had enough ASI production. (3) there is a significant influence between oxytocin massage on breast milk production in postpartum mothers in the working area of the Public Health Center in Cikeusik, Pandeglang district. It is expected that the puskesmas will be able to increase public knowledge and insight, especially on how to increase the amount of milk production in postpartum mothers by conducting counseling about oxytocin massage in increasing the amount of milk production.